As implicações do termo Verstehen na Psicologia Descritiva e analítica de Wilhelm Dilthey - Barbosa, Vinicius Aredes (2024)
The word Verstehen, during the 19th and 20th centuries, was widely used in philosophical currents such as hermeneutics, history and phenomenology. Even today, its conceptualization is discussed and applied in the scientific context of areas such as psychology, philosophy, law and others. This fact highlights its relevance and points to the need for continued investigation. Thus, the objective of this work is to discuss the implications of Verstehen in the work Descriptive and Analytical Psychology, 1894, by Wilhelm Dilthey. It is known that the author is at the basis of the thinking of the social sciences that developed in the 20th century and that this concept was present throughout his theoretical construct. However, it is in the undertaking of his descriptive psychology that the clearest elucidation of the methodological intentions that the concept was responsible for in Dilthey's general work begins. In this way, for proper understanding, we intend to present the context of the issues present in the philosopher's discussions; situate the broader construct of his work; and discuss the implications of the term in relation to the objective of the human sciences and in defense of its current relevance in the social and scientific scenario